2016
DOI: 10.1007/s11165-016-9518-x
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Formation at Preschool from a Socio-materiality Perspective

Abstract: International audienceThe paper is set in socio-material farming to offer a way of conceptualising actions and interactions of children in preschool involved in the understanding of scientific concepts. A model of early science education about the physical phenomena of shadow formation is implemented in group work in a French context. The research involved 44 children (13 females and 31 males) of 5–6 years old. The research design was organised in three video recording steps: pre-test, teaching session and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
0
6
0
6
Order By: Relevance
“…The literature on scientific activities in education and in particular in early childhood is relatively recent (Impedovo et al 2017). Most of the studies about how to implement and analyze STEM in education deal with elementary, middle or high school (e.g., Smyrnaiou et al 2015).…”
Section: Argumentation In Scientific Activitiesmentioning
confidence: 99%
“…The literature on scientific activities in education and in particular in early childhood is relatively recent (Impedovo et al 2017). Most of the studies about how to implement and analyze STEM in education deal with elementary, middle or high school (e.g., Smyrnaiou et al 2015).…”
Section: Argumentation In Scientific Activitiesmentioning
confidence: 99%
“…As is seen, when the concept of light is examined through a broad perspective, it is possible to tell that it has a substantial concept network potentially. In research studies carried out with preschool children (Delserieys et al, 2017a;Delserieys et al, 2017b;Delserieys et al, 2018;Gallegos-Cázares et al, 2009;Herakleioti & Pantidos, 2016;Hsu et al, 2011;Impedovo et al, 2017;Pantidos et al, 2017), it is observed that research mostly focus on their explanations on the formation of shadows. In spite of this, there are a few studies based on (Hsu et al, 2011;Ntalakoura & Ravanis, 2014;Ravanis et al, 2013) that show how young children structure (Çakır & Uludağ, 2019) concepts of light in their minds and what educational practices affect this process.…”
Section: The Present Researchmentioning
confidence: 99%
“…The environment brings mediational opportunities for learning, through the framework of socio-material perspective (Impedovo, Delserieys-Pedregosa, Jégou, & Ravanis, 2017). Through this perspective, the educational opportunities, the educators, learners and the environment are inseparable as educational agents.…”
Section: Mediational Opportunitiesmentioning
confidence: 99%